Morphological evaluation of microcellular foamed composites developed through gas batch foaming integrating Fused Deposition Modeling (FDM) 3D printing technique. Issue 6 (November 2021) - Radhakrishna, G; Dugad, Rupesh; Gandhi, Abhishek
In this article, the development of microcellular structure foams has developed by integrating the two successful and existing technologies, namely CO2 gas batch foaming and Fused Deposition Modeling (FDM) 3D printing technique. It is a novel approach to manufacture complex design porous products for customized applications. The eventual cell morphologies of the extruded 3D printing filament depends on the process parameters pertaining to both microcellular foaming and 3D printing processes. Further, morphological study has been conducted to evaluate the cell morphologies of the 3D printing filament developed through customized FDM setup. During this process, the significance of various process parameters including saturation pressure, saturation time, desorption time, feed rate and extrusion temperature were thoroughly studied. To pursue this study base material used was acrylonitrile butadiene styrene (ABS). The 3D printed filaments consisted of cells with an average cell size in the range of 2.3–276 µm and the average cell density in the range of 4.7 × 10 4 to 4.3 × 10 9 cells/cm 3 . Finally, it has found that by controlling the process parameters different cell morphologies can be developed as per the end application.